2017
DOI: 10.1371/journal.ppat.1006457
|View full text |Cite
|
Sign up to set email alerts
|

Potassium is a key signal in host-microbiome dysbiosis in periodontitis

Abstract: Dysbiosis, or the imbalance in the structural and/or functional properties of the microbiome, is at the origin of important infectious inflammatory diseases such as inflammatory bowel disease (IBD) and periodontal disease. Periodontitis is a polymicrobial inflammatory disease that affects a large proportion of the world's population and has been associated with a wide variety of systemic health conditions, such as diabetes, cardiovascular and respiratory diseases. Dysbiosis has been identified as a key element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 78 publications
4
31
0
5
Order By: Relevance
“…Fig 2). We observed similar results in our two previous 123 studies on periodontitis progression 23 and the effect of ion potassium in functional dysbiosis of the 124 oral microbiome 24 . As a whole, these results seem to indicate that the presence of cortisol leads to a 125 community-wide response very similar to the one observed in vivo during periodontitis.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Fig 2). We observed similar results in our two previous 123 studies on periodontitis progression 23 and the effect of ion potassium in functional dysbiosis of the 124 oral microbiome 24 . As a whole, these results seem to indicate that the presence of cortisol leads to a 125 community-wide response very similar to the one observed in vivo during periodontitis.…”
supporting
confidence: 84%
“…We included also results from 2 previous studies one on periodontal disease progression 23 and another 222 where we showed that potassium was a crucial signal in dysbiosis 24 To assess the effect that cortisol has on the oral microbiome we performed metatranscriptome 249 analysis of a biological triplicate of subgingival dental plaque from a periodontally healthy subject. 250…”
Section: Manuscript 159mentioning
confidence: 99%
“…The extent to which K + release from the microbiota present in the same habitat as the zoospores can mediate zoospore aggregation remains to be evaluated. Potassium seems to play a key role in the displacement of bacteria, the physical composition of microbiota [25] and pathogenic processes [26]. The electrical signalling mediated by potassium The red window indicates the area of the chamber taken into account in the analysis of zoospore tracking and measurement of the spatio-temporal concentration of potassium.…”
Section: Sources Of K + Gradients In the Natural Environmentmentioning
confidence: 99%
“…To what extent K + release by microbiota sharing the zoospore habitat could mediate their aggregation remains to be evaluated. Potassium appears to be key in the displacement of bacteria, in the physical composition of microbiota [24] and in the process of pathogenesis [25]. Electrical signaling mediated by potassium ion channels regulates cell-cell dialogs within a bacterial biofilm with potassium driving attraction of distant cells of different species [24].…”
Section: Discusssionmentioning
confidence: 99%